Modeling and Rehabilitation of Non-Ductile Spatial RC Columns - Galal, Elmandooh Mohamed Ibrahim (My University, 2002)
In frame structures, the multi-directional motion of an earthquake has a significant effect on the structure response. The columns, especially those at the building corners, are subjected to biaxial bending from combined longitudinal, transverse, and torsional motion of the structure, with added axial loads due to overturning. Moreover, the variation of the axial forces may be independent of the variation of the other lateral forces.
The non-ductile response of structural elements, particularily columns, has been the cause of numerous failures during earthquakes. The non-ductile behaviour of reinforced concrete columns arises from different causes such as insufficient anchorage length and bond for the longitudinal steel bars with concrete, insufficient confinement, or inadequate shear strength.
The objective of this research program is to analytically and experimentally evaluate the non-linear behaviour of non-ductile reinforced concrete columns under lateral cyclic deformations. The experimental data was used to verify the analytical predictions.
The analytical phase of this study included the development of an upgraded 3D beam-column element based on lumped plasticity modelling. The model accommodates flexural response by quadrilinear force-deformation relationship, and shear response by strength and stiffness degrading relationship. The model takes into account the effect of axial load variation on lateral deformation and its interaction with biaxial moments and shear, which is an important contribution.
The 3D model was validated using experimental data available in the literature by several independent researchers for reinforced concrete columns. The calculated and experimetnal results were encouragingly close, especially considering the complexity of the response. The effect of different axial load variation paths on the response of cyclically loaded columns was studied.
A new analytical procedure to obtain the moment-rotation and force-deflection relationships for reinforced concrete columns was developed. These relationships were used as input data for the 3D element. This procedure uses the basic mechanical and geometrical properties of the element. This procedure uses the basic mechanical and geometrical properties of the element. It takes into consideration the effect of bond-slip of tensile bars, buckling of compression bars as well as flexure and shear deformations. This procedure was verified using available experimental data. The comparision showed good agreement. A parametric study to evaluate the effect of variation in section and material properties was also conducted.
The experimental phase of this study included testing three reinforced concrete short columns under cyclic lateral loads and constant axial load. The first specimen, which represents columns designed according to current code (CSA A23.3-94), failed in a non-ductile shear manner. The second specimen was identical to the first one but rehabilitated using anchored carbon fibre reinforced polymers (CFRP). A significant increase in the displacement ductility of the column was achieved. The third specimen represents a non-ductile short column designed according to pre-1970 codes and rehabilitated using anchored CFRP wraps. Increased ductility was achieved. Two different techniques to reduce concrete bulging at column sides were evaluated in the two rehabilitated specimens; namely, by using through steel rods and fibre anchors. Both techniques proved to be effective.
Keywords: Civil and Environmental Engineering; Civil and Environmental Engineering